PHILOSOPHICAL EXPLORATION OF PANDEMIC EPISTEMOLOGY - Imam Wahyudi; Rangga Kala Mahaswa (UIN Raden Mas Said Surakarta, 2021)
The Covid-19 pandemic has significantly shifted people’s behavior in various aspects of life. As a contemporary discourse, pandemic needs to be understood with a more comprehensive approach. This article contains two common perspectives on pandemics: naturalistic perspective, which views pandemics either as individual microscopic entities or as a life process; and socio-constructivist, which views pandemics as non-natural disasters and public discourse consensus. The second view is getting more public attention because of its closeness to sociological experiences amid information uncertainty, which formed from the prevalence of disinformation, fake news, knowledge vulnerabilities, and society’s digital-virtual freedom. However, there is also undeniable confusion about information or particular political interests from government authorities or the scientific community. The post-truth dimension also influences the socio-epistemic constellation of society in understanding the pandemic. This article aims to open a scientific-philosophical discussion and produce an epistemological framework for understanding the pandemic based on a more rigorous epistemological review and then can be a post-pandemic policy consideration.